THE LEVEL OF COMMUNITY PARTICIPATION ON FOREST AND LAND REHABILITATION IN THE VILLAGE WISOLO SOUTH DOLO DISTRICTSIGI DISTRICT - Dhea Ardaeni Yasin (Tadulako Social Science and Humaniora Journal, 2023)
Forest and Land Rehabilitation (RHL) based on community participation is the key to successful forestry development. Community participation can be increased with community empowerment programs to achieve independence in Forest and Land Rehabilitation. This activity is an effort to motivate the growth of awareness and attention of all components of society to realize environmental improvements so that the function of forest resources can develop productively and optimally. The purpose of the study is to determine the level of community participation in the planning, implementation, utilization, monitoring, and evaluation stages of forest and land rehabilitation activities in Wisolo Village, South Dolo District, Sigi Regency. Study This uses method qualitative and quantitative descriptive Data collection was carried out through interview techniques using questionnaires and field surveys of respondents and information, determination respondents This is done in a way purposive sampling or technique taking sample data source with consideration certain ie the data source is considered to know best about what to expect. Based on the results of this research, there were 23 groups and communities involved in the rehabilitation of the Forest and Land in Wisolo Village. Based on the results, it shows that from 1 2 questions the average respondent's answer ranges from 75% - 88.043%, meaning participating - very participating, and the total of all over question whole as much as 83.96% which means (Highly Participate).